Determination of Sugars in Soft Drinks by High Performance Liquid Chromatography - Augustin, M. A.; Khor, K. L. (1986)
The fructose, glucose and sucrose contents of selected soft' drinks available in Malaysian markets were determined by high performance liquid chromatography (HPLC). The soft drinks tested had a soluble sugar content of between 8.5 to 15.3 g 100 ml- 1 • The average fructose, glucose and sucrose contents werefound to be in the ranges of 0 - 6. 7, 0 - 6.9 and 0 - 10.5 g 100 ml I respectively. The content of individual sugars were found to be more variable than the content of total sugar in different samples of a specific soft drink.